Perilaku Petani Terhadap Agribisnis Jagung Lamuru Di Desa Uiasa Kecamatan Semau Kabupaten Kupang - Martina L. Tukan; Leta R. Levis; Wiendiyati Wiendiyati (Undana Press, 2019)
Research on farmer's behavior towards lamuru agribusiness in the Village of the Semau District of Kupang Regency has been carried out from December to January 2019. The purpose of this study was to determine the behavior of farmers towards the agro-business of lamuru corn in the village of Uiasa, as well as the constraints that influenced the behavior of farmers in the lamuru corn agribusiness in the village of Uiasa. This research was conducted by survey method, determining the location of the study was determined by Purposive Sampling. Farmers sampled at the study site were 70 respondents from 238 populations. Data analysis was included with a descriptive analysis of the Likert scale approach. The results showed that farmer behavior towards corn farming was in the neutral category with an average score of 2.67 with a percentage of 53.49%, meaning that the behavior of farmers in carrying out a farming activity at the research site was mediocre without any good change the farmer. This condition occurs because farmers in the research area in running the lamuru corn agribusiness have limited human resources in terms of management of lamuru corn agribusiness, the attitude of farmers who do not support the lamuru corn agribusiness program so that productivity is expected to be inappropriate and will also affect the level of income and welfare of farmers. The social factors that influence corn farming, namely the level of education, the number of family dependents, mutual cooperation and conformity are still the main challenges for farmers in the Village in the running of the lamuru corn agribusiness. Penelitian tentang perilaku petani terhadap agribisnis jagung Lamuru di Desa Uiasa Kecamatan Semau Kabupaten Kupang telah dilaksanakan dari bulan Desember hingga Januari 2019. Tujuan dari penelitian ini adalah untuk mengetahui perilaku petani terhadap agribisnis jagung lamuru di Desa Uiasa, serta kendala-kendala yang mempengaruhi perilaku petani dalam agribisnis jagung lamuru. Penelitian ini dilakukan dengan metode survei, penentuan lokasi peneltian ditentukan secara Purposive Sampling. Petani sampel di lokasi penelitian sebanyak 70 responden dari 238 populasi. Data dianalisis secara deskriptif dengan pendekatan skala Likert. Hasil penelitian menunjukan bahwa perilaku petani terhadap usahatani jagung lamuru berada pada kategori moderasi dengan pencapaian skor rata-rata 2,67 dan pencapaian skor maksimum 53,49 %, artinya perilaku petani dalam menjalankan suatu aktivitas usahatani di lokasi penelitian biasa-biasa saja. Kondisi ini terjadi karena petani di daerah penelitian dalam menjalankan agribisnis jagung lamuru memiliki keterbatasan sumberdaya manusia dalam hal manajemen pengelolaan agribisnis jagung lamuru, sikap petani yang tidak mendukung program agribisnis jagung lamuru sehingga produktivitas diharapkan tidak sesuai dan juga akan mempengaruhi tingkat penghasilan serta kesejahteraan petani. Faktor sosial yang mempengaruhi usahatani jagung yaitu tingkat pendidikan, jumlah tanggungan keluarga, gotong-royong dan konformitas masih menjadi tantangan utama bagi petani di Desa Uiasa dalam menjalankan agribisnis jagung lamuru.